Royal Economic Society - (:unkn) unknown (My University, 2026)
The RES is a learned society and membership organization founded in 1890. We publish two major journals, the Economic Journal and the Econometrics Journal, and organize events including an annual conference. We encourage excellence, diversity and inclusion in all activities. We welcome new members and seek to represent the interests of economists in all areas of the discipline and all parts of the world.